Design and in vitro Evaluation of Fluvoxamine Nanosuspension using PVA as Stabilizing Agent (Asian Journal of Pharmaceutics (AJP), 2021)
Introduction: Poor aqueous solubility and low dissolution rates are the initial drawback for the majority ofupcoming and existing biologically active compounds. Materials and Methods: Fluvoxamine (API), otherexcipients such as PVA, SLS, Tween 80, and methanol. Fluvoxamine is a poorly water-soluble drug and itsbioavailability is very low. The present study was to increase the solubility and dissolution rate of Fluvoxamineby formulating nanosuspensions by Emulsification solvent evaporation method. Results and Discussions: Theformulation nanosuspenison was subject to zeta potential, particle size analysis, drug content, and in vitro drugrelease studies. The entrapment efficiency of all the formulations was within 95.78–98.16%, from the drug releasestudies, The NF6 formulation was optimized and it shows maximum drug release (99.02%) at a shorter periodof time than remaining formulations. The average particle size of the optimized formulation was found to be110 nm. Conclusion: The research showed that enhanced dissolution rate by reduced in particle size, which,in turn, increases the dissolution rate and oral bioavailability of fluvoxamine by formulating nanosuspensions.Formulations were found to physically stable with PVA as the stabilizing agent.